2013
DOI: 10.4161/cc.23103
|View full text |Cite
|
Sign up to set email alerts
|

Diploid, but not haploid, human embryonic stem cells can be derived from microsurgically repaired tripronuclear human zygotes

Abstract: (2013) Diploid, but not haploid, human embryonic stem cells can be derived from microsurgically repaired tripronuclear human zygotes, Cell Cycle, 12:2, 302-311,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
17
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(17 citation statements)
references
References 51 publications
(66 reference statements)
0
17
0
Order By: Relevance
“…However, since all hESC lines have chromosomal abnormalities, the risks involved in this method need to be evaluated [33]. In our previous study, we also indicated that the diploid hESC lines can be derived from 3PN zygotes when one pronuclear is removed [8], and Jiang et al subsequently proved our results [9]; however, the lower efficiency limited the development of this method. Here, we have developed a new culture system to promote the application of 3PN zygotes.…”
mentioning
confidence: 62%
See 4 more Smart Citations
“…However, since all hESC lines have chromosomal abnormalities, the risks involved in this method need to be evaluated [33]. In our previous study, we also indicated that the diploid hESC lines can be derived from 3PN zygotes when one pronuclear is removed [8], and Jiang et al subsequently proved our results [9]; however, the lower efficiency limited the development of this method. Here, we have developed a new culture system to promote the application of 3PN zygotes.…”
mentioning
confidence: 62%
“…Very often (5%-7% incidence rate), two sperms enter the oocyte, forming polyspermic zygotes (also named 3PN zygotes, because three pronuclear ones are observed in these zygotes). In a previous study, Fan et al demonstrated that the cytoplasm of 3PN zygotes can reprogram human somatic cells by nuclear transfer technology, indicating that the cytoplasm of 3PN zygotes is comparable to that of normal zygotes [8], and these results were further corroborated by Kawamura et al [24]. Therefore, the concern was whether diploid zygotes could be obtained after the removal of a redundant pronucleus.…”
Section: Fig 4 Effect Of Egf-bdnf-igf-1 Supplement On the Chromosommentioning
confidence: 87%
See 3 more Smart Citations